Macular Dystrophies - Querques, Giuseppe; Souied, Eric (Springer International Publishing : Imprint: Springer, 2016)
This book provides the ophthalmologist with the most recently available data on the macular dystrophies, a group of many different inherited or sporadic eye conditions linked by a problem with photoreceptors or other structures of the central retina. Internationally recognized experts in the field present the latest evidence and discuss their own personal experiences with regard to each of the principal dystrophies as well as some very rare entities. Topics covered include molecular biology, state-of-the-art diagnostic techniques, and the newest treatment options, including still experimental therapies. Attention is also devoted to a range of issues that continue to be debated. The editors have taken care to ensure that chapters are of a uniformly high standard while not sacrificing the originality of the individual authors. Macular Dystrophies will fully acquaint the reader with both the latest research findings and the current and emerging approaches to diagnosis and treatment.